An analytical approach to study kinematics of shock waves in a dusty, cylindrical gas flow. Issue 12 (7th November 2022) - Palo, Nishi Deepa; Jena, J.; Chadha, M.
Abstract: In this article, the developmental behaviour of one‐dimensional shock waves in a dusty, rotational flow has been considered. The mathematical scheme based on the kinematics of one‐dimensional fluid flow for the derivation of an infinite hierarchy of transport equations has been employed. The scheme is a truncation procedure which helps to examine the system of transport equations in a simple form. The first two approximations are studied to illustrate the effects of dust and rotational parameters. Abstract : In this article, the developmental behaviour of one‐dimensional shock waves in a dusty, rotational flow has been considered. The mathematical scheme based on the kinematics of one‐dimensional fluid flow for the derivation of an infinite hierarchy of transport equations has been employed. The scheme is a truncation procedure which helps to examine the system of transport equations in a simple form. The first two approximations are studied to illustrate the effects of dust and rotational parameters.